DS02R1: Improvements to Atomic Bomb Survivors' Input Data and Implementation of Dosimetry System 2002 (DS02) and Resulting Changes in Estimated Doses. Issue 1 (January 2017) - Cullings, H.M.; Grant, E.J.; Egbert, S.D.; Watanabe, T.; Oda, T.; Nakamura, F.; Yamashita, T.; Fuchi, H.; Funamoto, S.; Marumo, K.; Sakata, R.; Kodama, Y.; et al.
Abstract : Abstract: Individual dose estimates calculated by Dosimetry System 2002 (DS02) for the Life Span Study (LSS) of atomic bomb survivors are based on input data that specify location and shielding at the time of the bombing (ATB). A multi-year effort to improve information on survivors' locations ATB has recently been completed, along with comprehensive improvements in their terrain shielding input data and several improvements to computational algorithms used in combination with DS02 at RERF. Improvements began with a thorough review and prioritization of original questionnaire data on location and shielding that were taken from survivors or their proxies in the period 1949–1963. Related source documents varied in level of detail, from relatively simple lists to carefully-constructed technical drawings of structural and other shielding and surrounding neighborhoods. Systematic errors were reduced in this work by restoring the original precision of map coordinates that had been truncated due to limitations in early data processing equipment and by correcting distortions in the old (WWII-era) maps originally used to specify survivors' positions, among other improvements. Distortion errors were corrected by aligning the old maps and neighborhood drawings to orthophotographic mosaics of the cities that were newly constructed from pre-bombing aerial photographs. Random errors that were reduced included simple transcription errors and mistakes in identifying survivors' locations on the old maps. Terrain shielding input data that had been originally estimated for limited groups of survivors using older methods and data sources were completely re-estimated for all survivors using new digital terrain elevation data. Improvements to algorithms included a fix to an error in the DS02 code for coupling house and terrain shielding, a correction for elevation at the survivor's location in calculating angles to the horizon used for terrain shielding input, an improved method for truncating high dose estimates to 4 Gy to reduce the effect of dose error, and improved methods for calculating averaged shielding transmission factors that are used to calculate doses for survivors without detailed shielding input data. Input data changes are summarized and described here in some detail, along with the resulting changes in dose estimates and a simple description of changes in risk estimates for solid cancer mortality. This and future RERF publications will refer to the new dose estimates described herein as "DS02R1 doses."